2023
DOI: 10.1109/jstars.2023.3236159
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for High-Frequency Vibration of SAR Imaging in the Terahertz Band Based on Linear Chirplet Transform and Empirical Mode Decomposition

Abstract: Synthetic aperture radar (SAR) in Terahetz (THz) band is very important and valuable in the field of radar signal processing, and it is much sensitive to the high-frequency vibration of the platform due to the short wavelength. In this paper, the high-frequency vibration is characterized as multi-component sinusoidal frequency modulated (SFM) signal, and the parameters estimation method based on the linear chirplet transform (LCT) and empirical mode decomposition (EMD) is proposed to compensate the high-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with previous studies [15,16] that have shown that the combination of EMD and wavelet threshold denoising methods can effectively remove noise from signals. However, our proposed method achieved better filtering performance, which may be attributed to the use of the EMD method for signal decomposition and the optimized parameter settings.…”
Section: Comparison Of Different Filtering Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous studies [15,16] that have shown that the combination of EMD and wavelet threshold denoising methods can effectively remove noise from signals. However, our proposed method achieved better filtering performance, which may be attributed to the use of the EMD method for signal decomposition and the optimized parameter settings.…”
Section: Comparison Of Different Filtering Methodssupporting
confidence: 93%
“…During the simulation, it was found that using EMD to extract only the signal IMF would cause peak reduction and offset, resulting in significant deviations from the original signal. To address this issue, it was necessary to extract the effective parts from other IMF signals and superimpose them with the [16] 0.0063 0.9972 signal-only IMF. On the other hand, the wavelet threshold denoising method required the selection of the optimal wavelet basis, decomposition level, and thresholding rule, which was time-consuming.…”
Section: Comparison Of Different Filtering Methodsmentioning
confidence: 99%
“…Moreover, many studies have focused on parameter estimation for vibration. Recently, various algorithms have been proposed for parameter estimation and compensation of high-frequency vibrations [22]- [26]. The aforementioned studies mainly focused on refocusing and parameter estimation for oscillation of ships and highfrequency vibrations of SAR platforms.…”
Section: Introductionmentioning
confidence: 99%